Analysis of Students' Mathematical Communication Skills in the Perspective of Gender and Personality Type - Gunur, Bedilius; Metrisna Restu; Eufrasi Jeramat; Ramda, Apolonia Hendrice (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2024)
This study aims to describe mathematical communication skills in terms of gender and personality type of grade VII students of SMPN 5 Langke Rembong. This research is qualitative research using a descriptive approach. The study subjects consisted of 4 people with details of 2 male subjects and 2 female subjects with introvert-extrovert personality type. The data collection techniques used are tests, questionnaires, and documentation. Data analysis techniques using the Miles & Huberman model data analysis, namely data reduction, data presentation, and conclusions. The validity of the data in this study used triangulation (sources and techniques). The results showed that both male and female students were able to express mathematical ideas in writing correctly and completely, were able to evaluate mathematical ideas in solving the problem correctly, and the solution steps were written sequentially, completely, and correctly, and were also able to write the conclusion of solving the problem given. However, when viewed from the personality type of male subjects with extroverted types, they were less superior in evaluating mathematical ideas, especially in the aspect of writing the formula used to solve the problem.